Antioxidant content in traditional barobbo foods of yellow corn and white pulut corn - Wijayanti Burhanuddin; Sukmawati Sukmawati; Hikmawati Mas'ud (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
In 2012, around 8.2 million deaths were caused by cancer. More than 30% of cancer deaths are caused by five behavioral and dietary factors. One of the factors is the lack of consumption of vegetables and fruit. One way to prevent cancer is to consume foods rich in antioxidants. Sources of antioxidants can be obtained from vegetables and fruits. Barobbo is a traditional food from South Sulawesi made from corn. Barobbo is still demand by the public. Corn is in second place after bananas for the people of South Sulawesi to be processed into food, both in the form of cakes, traditional foods, and vegetable blends. The problem formulation of this research is knowing how much the antioxidant content in traditional foods of barobbo yellow corn and white pulit corn. This study aims to analyze the antioxidant content in traditional foods of yellow corn and white pulut corn barobbo. This research is laboratory research. The research was carried out in two stages, the first stage of making barobbo to determine the standard of serving and the second stage of making barobbo, which was to analyze the antioxidant content of barobbo, yellow corn and white pulut corn. The conclusion of this study is that the content of yellow corn, vitamin A in 100 grams of barobbo is 353 μg and vitamin C as much as 10 mg. While the content of vitamin A barobbo in 100 grams of white pulut is 273 μg and vitamin C as much as 26.4 mg. For further studi this recomended to make a temperature measurement on the baroobo cooking process so that the temperature of making barobbo can be measured. In addition, barobbo is recommended for public consumption because it has high levels of vitamin A and vitamin C.